If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(5 + -11) + 15 = 3(g + -7) + -7 Combine like terms: 5 + -11 = -6 2(-6) + 15 = 3(g + -7) + -7 Multiply 2 * -6 -12 + 15 = 3(g + -7) + -7 Combine like terms: -12 + 15 = 3 3 = 3(g + -7) + -7 Reorder the terms: 3 = 3(-7 + g) + -7 3 = (-7 * 3 + g * 3) + -7 3 = (-21 + 3g) + -7 Reorder the terms: 3 = -21 + -7 + 3g Combine like terms: -21 + -7 = -28 3 = -28 + 3g Solving 3 = -28 + 3g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-3g' to each side of the equation. 3 + -3g = -28 + 3g + -3g Combine like terms: 3g + -3g = 0 3 + -3g = -28 + 0 3 + -3g = -28 Add '-3' to each side of the equation. 3 + -3 + -3g = -28 + -3 Combine like terms: 3 + -3 = 0 0 + -3g = -28 + -3 -3g = -28 + -3 Combine like terms: -28 + -3 = -31 -3g = -31 Divide each side by '-3'. g = 10.33333333 Simplifying g = 10.33333333
| 4(5+a)=0 | | 2(x-3)+3y=5y-2(3-5x)fory | | (x)=[[x]]-2 | | F(x)=[[x]]-2 | | 3d+8=d+20 | | z=x+(z-x) | | 1.98=x^2+x | | lg(3x+20)=2 | | 4w+3=20-6a | | 8(-4+y)= | | 9r-5=85 | | 101+c= | | 17(2)-16= | | 2p-3=-19 | | -(-11+b)=16 | | 256(5)+3(11)= | | 5x-7=8x-58 | | 6+4=4 | | -3-7=-x-2 | | 5(-2+n)=35 | | Ix+2y=0 | | 5b-1=-31 | | 6(x+8)+3x=-2(x-2) | | Y-6=4(x-12) | | y=2x-x-7 | | 6(x+8)+3a=-2(x-2) | | 40+3x=73 | | 7x+2=-3+2x+25 | | 2*ln(x)-ln(4)=0 | | -40-6k=-3(-k+6)+5 | | (2x+10)=(120) | | 26x=180+24-35 |